Nutritional Status of Elementary School Children in Coastal and Mountains Areas in Kian Darat District, Eastern Seram Regency - Muhamad A Buatan; Erynola Moniharapon; Helen C D Tuhumury (Jurnal Agrosilvopasture-Tech, 2023)
is study aims to determine the nutritional status of elementary school-aged children in coastal and mountainous areas in Kian Darat District, East Seram Regency. Samples in coastal villages are Kilga, Kian, Rumfakar, and Kilaba villages, while mountain villages are Rumoga and Rumbou villages. In each village, 5 children were selected as respondents. The respondent's characteristic data were analyzed descriptively. Determination of nutritional status based on BMI/U anthropometry and determination of nutritional status based on Minister of Health Regulation No. 2 of 2020, namely the Child Anthropometry Standard. Based on the results of the study, it can be concluded that the distribution of nutritional status of elementary school-aged children in coastal areas is as follows: Normal nutritional status is 50%, very thin 10%, lean 30%, and obese 10% while in mountainous areas are: Normal nutritional status as much as 80%, 10% thin and 10% very thin.